Bacterial community dissimilarity between the surface and subsurface soils equals horizontal differences over several kilometers in the western Tibetan Plateau - Haiyan Chu; Huaibo Sun; Binu M. Tripathi; Jonathan M. Adams; Rong Huang; Yangjian Zhang; Yu Shi (Environmental Microbiology, 2016)
Summary Many studies have investigated patterns in the near‐surface soil microbial community over large spatial scales. However, less is known about variation in subsurface (15–30 cm of depth) microbial communities. Here we studied depth profiles of microbial communities in high‐elevation soils from Tibet. The relative abundance of Acidobacteria, Chloroflexi and Alphaproteobacteria was higher in near‐surface layers, while the relative abundance of Actinobacteria, Gemmatimonadetes and Betaproteobacteria was higher in the subsurface samples. The microbial community structure was distinct between the surface and subsurface soil layers, strongly correlating with variation in total carbon (TC) and carbon to nitrogen ratio (C/N). The differences in the microbial community between the layers were about the same as the horizontal differences between sites separated by many kilometers. Overall, we found that TC and C/N were the best predictors for both surface and subsurface microbial community distribution. Exploration of the relative contribution of distance and environmental variables to community composition suggests that the contemporary environment is the primary driver of microbial distribution in this region. Reflecting niche conservatism in evolution, the microbial communities in each soil site and layer tended to be more phylogenetically clustered than expected by chance, and surface soil layer samples were more likely to be clustered than subsurface samples.